If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + 1 + -1b = 1 Reorder the terms: 1 + 7b + -1b = 1 Combine like terms: 7b + -1b = 6b 1 + 6b = 1 Add '-1' to each side of the equation. 1 + -1 + 6b = 1 + -1 Combine like terms: 1 + -1 = 0 0 + 6b = 1 + -1 6b = 1 + -1 Combine like terms: 1 + -1 = 0 6b = 0 Solving 6b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '6'. b = 0 Simplifying b = 0
| x+7=-2(4x+10) | | 7-9x=46-30x | | 184-4x=41x+19 | | 6+x=-13 | | -42+y+2=44 | | y^2+6y-7=17 | | -x^2+6x-5=y | | -2n-n=-12 | | -7+6=x | | 9-10x=89-24x | | 5t-3t+8+4t-2=42 | | x-4+3x=12 | | x^2-2-20=0 | | r-4+6r=-4 | | 64s^2-4t^2= | | -3(2x-1)=x+10 | | -16x=-8+24x^2 | | 3x+9=-111-9x | | -2x=36 | | 5x=2y+4 | | -5-3x=5x+10 | | x^2-12x+c=0 | | 8x^2-24x-32=0 | | X-0.2x=18 | | -2x^2+18=0 | | w^2+18w+81= | | 12x+71=5 | | 5x+193=13x-7 | | 3x+x=52 | | 12xy=384 | | 6a-a^2=48 | | 215-2x=34x+23 |